2022
DOI: 10.1007/s12325-022-02301-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Japanese Patients with Dysmenorrhea or Endometriosis-Associated Pelvic Pain Treated with Extended Regimen Ethinylestradiol/Drospirenone in a Real-World Setting: A Prospective Observational Study

Abstract: Introduction Dysmenorrhea and endometriosis are common gynecologic disorders among women of reproductive age that significantly impact health-related quality of life (HRQL) as well as productivity. Although there are treatment options listed in Japanese guidelines, a gap remains in unmet medical needs for maximizing treatment outcome. The extended regimen of ethinylestradiol and drospirenone (EE/DRSP) (taken daily for up to 120 consecutive days) has been available in Japan for treating dysmenorrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our systematic review also showed that Drospirenone Ethinylestradiol Tables (II) had a good safety profile (such as low risk in thrombus, weight gain, or water-retention), good tolerability, and a low overall risk of adverse events compared to other positive controls. The study in Japan ( 26 ) also validated the safety and efficacy of Drospirenone Ethinylestradiol in patients with Endometriosis-associated pelvic pain and Dysmenorrhea. The reasons may be that the low estrogenic dose of Drospirenone Ethinylestradiol Tables (II) could reduce estrogen-related adverse effects; the pharmacological activity of Drospirenone Ethinylestradiol Tables (II) itself (no androgenic activity, anti-androgenic activity, and anti-mineralocorticoid activity), and the more stable overall sex hormone levels resulting from the 24/4-day regimen may also reduce the overall incidence of adverse events.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our systematic review also showed that Drospirenone Ethinylestradiol Tables (II) had a good safety profile (such as low risk in thrombus, weight gain, or water-retention), good tolerability, and a low overall risk of adverse events compared to other positive controls. The study in Japan ( 26 ) also validated the safety and efficacy of Drospirenone Ethinylestradiol in patients with Endometriosis-associated pelvic pain and Dysmenorrhea. The reasons may be that the low estrogenic dose of Drospirenone Ethinylestradiol Tables (II) could reduce estrogen-related adverse effects; the pharmacological activity of Drospirenone Ethinylestradiol Tables (II) itself (no androgenic activity, anti-androgenic activity, and anti-mineralocorticoid activity), and the more stable overall sex hormone levels resulting from the 24/4-day regimen may also reduce the overall incidence of adverse events.…”
Section: Discussionmentioning
confidence: 85%
“…The results showed the effectiveness of Drospirenone and Ethinylestradiol Tablets (II) in Chinese women with dysmenorrhea. Another study in Japan involved 315 patients (mean age 28.9 years) with dysmenorrhea and 262 patients (mean age 31.3 years) with endometriosis showed that ethinylestradiol and drospirenone could improve QOL outcomes for patients with dysmenorrhea or endometriosis-associated pelvic pain ( 26 ). Evidence in our systematic review indicated that Drospirenone and Ethinylestradiol Tablets (II) could relieve dysmenorrhea and reduce the diameter of ovarian cysts when compared with before treatment, which was consistent with the above results.…”
Section: Discussionmentioning
confidence: 99%
“…The EHP-30 is a valid and reproducible measure of HRQoL in women with endometriosis, consisting of 30 questions divided into five categories: pain, control and powerlessness, social support, emotional well-being, and self-image [22,23]. The EQ-5D is a generic instrument for describing HRQoL in daily life, evaluating daily life in five dimensions: mobility, self-care, usual activities, pain/discomfort, and anxiety/depression [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this specific contraceptive preparation has been demonstrated to be clinically effective in the neuroendocrine control of specific areas of the central nervous system (CMNS), since it has been proposed for the treatment of premenstrual syndrome (PMS) or premenstrual dysphoric disorder (PMDD) [30]. Moreover, Yoshino et al [31] reported a great efficacy of the EE + DRSP combination on pain perception in sufferers of endometriosis and/or dysmenorrhea. Additionally, confirming the central modulatory role of DRSP, De Berardis et al [30] sustained that EE + drospirenone should be taken into consideration, not as a first-line treatment but reserved mainly for SSRI-resistant subjects so as to have a better action centrally.…”
Section: Discussionmentioning
confidence: 99%